Interdisciplinary approach to technical education - KROTKÝ, JAN; KORYTÁŘ, JINDŘICH; SIMBARTL, PETR (Journal of Education, Technology and Computer Science, 2016)
The authors introduce a realistic concept of innovation in teaching technical subjects at primaryschools with regard to sustainable development of industrial society. The concept is based onthe published results of an institutional survey carried within six organizations which are concernedwith teaching the educational area of Man and the World of Work and preparing teachersfor the area. The survey was conducted as a part of the project Erasmus +Activity 1, action strategicpartnerships for school education no. 2015-1-SK01-KA201-008942 and as a training of theinstitute of informal way of teaching at Techmania Technology Center. The innovation is seenespecially in interdisciplinary connections between subjects, implementation of new modern technologiesin teaching and support of informal education.